MY-CO SPACE: An artistic-scientific vision on how to build with fungi. Issue 1 (1st September 2022) - Meyer, V; Schmidt, B; Freidank-Pohl, C; Schmidts, C; Pfeiffer, S
Abstract: MY-CO SPACE is a collaborative work of the interdisciplinary SciArt collective MY-CO-X, that enables an artistic-scientific discussion about a future social significance of fungi for the creation of places and spaces. MY-CO SPACE is a wooden fungal sculpture that was built from biological materials and is biodegradable. The living space of approx. 20 sqm can be divided by the guests themselves into sleeping, reading, and working areas. It is not a completely enclosed space but a retreat and study space that lives from and deals with the contact with the outside world. This architectural artwork strives for a different point of view and a process of interaction in which humans are involved in a conscious as well as unconscious conversation with their environment, a point of view that tacitly implies a flattening of hierarchies between the different agents and authors - human as well as non-human. MY-CO SPACE is therefore a built reflection on a cooperation with biological systems that store, transform, and recycle organic matter and energy, and an exploration of fungi as a future lightweight building material resistant to fire, shock and water, and whose modification through biotechnology is possible. It is the urgency of the planetary situation and the issues we now face that require a holistic approach and close collaboration between art and science.